Cathedrals as agents of psychological health and well-being within secular societies: Assessing the impact of the Holly Bough service in Liverpool Cathedral - Francis, Leslie J. (HTS teologiese studies, 2020)
This study is designed to test the hypothesis that events like the Holly Bough service held in Liverpool Cathedral on the fourth Sunday of Advent that attracts a wide range of participants, including regular churchgoers and occasional (sometimes annual) visitors, contribute significantly to the psychological health and well-being of these participants. At the Holly Bough service held in 2019, a total of 383 participants (139 men, 229 women and 15 individuals who preferred anonymity) completed a recognised measure of psychological health and well-being (the Oxford Happiness Questionnaire) whilst they were waiting for the service to begin and again during a 5-min organ improvisation just before the close of the service. The data demonstrated a significantly higher score on the Oxford Happiness Questionnaire at time 2 than at time 1, suggesting that the experience of the service functioned as an agent of psychological health and well-being.Contribution: Situated within the science of cathedral studies, this paper confirms by means of a repeated-measure study that cathedrals promote psychological health; 383 participants at a Christmas service completed the same well-being measure before and after the service, with a significant increase in scores at time two.